Bone mineral density in pre-professional ballet dancers: A systematic review and meta-analysis - Wewege, M. A.; Ward, R. E. (Journal of Science and Medicine in Sport, 2018)
In the article, Wewege and Ward report the results of a systematic review of bone mineral densityin pre-professional female ballet dancers concerningly suggesting reduced upper limb bone densities compared to controls. Objectives: To quantitatively compare bone mineral density (BMD) outcomes between pre-professional female adolescent ballet dancers and control populations. Design: Systematic review and meta-analysis. Methods: Six electronic databases and relevant journals were systematically searched up to August 2017. Included articles examined BMD in adolescent females undergoing pre-professional ballet training and healthy age-matched controls with an available English full text. Dancers were aged 15-19 years and trained in ballet at least 10 h per week. BMD data were analysed via standardized mean difference to account for differences in reporting methods Results: From 3984 potential articles, 8 cross-sectional studies were accepted for inclusion, which compared 293 dancers (16.9 ± 0.8 years) to 333 controls (16.9 ± 0.9 years). No data were available from longitudinal studies. Dancers displayed lower BMD at the radius and higher BMD at the femoral neck, femoral trochanter and Ward`s triangle. No significant differences were observed in the lumbar spine or tibia. The overall study quality was low and heterogeneity was present in some analyses. Conclusions: This meta-analysis indicates that there may be a site-specific osteogenic effect of pre-professional classical ballet training in adolescent females, with a notable and concerning finding of reduced upper limb BMD compared to age-matched controls. Longitudinal cohort studies are required to confirm the effects of pre-professional ballet training on BMD during adolescence.